Implementasi Pendidikan Pendahuluan Bela Negara (PPBN) Dalam Pembentukan Karakter Mahasiswa Institut Transportasi Dan Logistik Trisakti - Markus Wibowo; E. Yochanan; Yuliantini Yuliantini; Olfebri Olfebri; Aang Gunawan; Rahmat Pannyiwi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Preliminary National Defense Education (PPBN) is a national strategic program aimed at developing the character of the younger generation, particularly university students, as agents of change and future national leaders. This study aims to analyze the implementation of PPBN in character development for students at the Trisakti Transportation and Logistics Institute, held at the Indonesian National Armed Forces Peacekeeping Mission Center (PMPP TNI) in Sentul. This study involved 659 students participating in the four-day PPBN program, which took place from January 22–25, 2026. The research method used was descriptive qualitative with an implementation study approach, through direct observation, documentation of activities, and analysis of PPBN learning materials. The results indicate that the implementation of PPBN significantly contributed to student character development, particularly in the aspects of discipline, responsibility, nationalism, leadership, cooperation, and mental resilience. Furthermore, PPBN activities increased students' understanding of the concept of non-military national defense, particularly in the context of the strategic role of the transportation and logistics sector in national resilience. This study concludes that PPBN is effective as a character education instrument in higher education and needs to be continuously integrated into the national education system.